Correlation Between Screen Time and Levels of Physical Activity and Health Indicators Among Adolescents at SMAN 2 Palangka Raya - Siskaevia Siskaevia; Zuly Daima Ulfa; Uswatun Hasanah; Garry William Dony; Yossita Wisman; Abdullah Abdullah; Iwan Noor Alamsyah; Bernisa Bernisa; Cahyo Nugroho Sigit (Jurnal Porkes, 2026)
Introduction: The high ownership of smartphones among teenagers in Central Kalimantan, supported by increasingly widespread internet penetration, indicates the intense use of digital technology in everyday life. A national survey reveals that the majority of adolescents have a screen time of more than 3 hours per day, reflecting the dominance of screen-based activities. This condition has the potential to encourage a shift from healthy lifestyles towards sedentary lifestyles. Methods : This study is a correlational study with a cross-sectional approach in July-August 2025 involving 151 students from SMAN 2 Palangka Raya using simple random sampling. The inclusion criteria used were students of SMAN 2 Palangka Raya aged 14-17 years who had provided informed consent. Instruments used included the Screen Time Questionnaire, International Physical Activity Questionnaire, Pittsburgh Sleep Quality Index, Patient Health Questionnaire Adolescent, BMI measurement sheet, and blood pressure recording. Then, the type of data used was ordinal, which was analyzed using Somers' d, with SPSS version 25. Results: There was a significant relationship between sleep quality p (0.000 <0.05), d (-0.181), mental health p (0.003<0.05), d (0.199), and BMI p (0.032 < 0.05), d (0.161). Meanwhile, no significant relationship was found in other variables (p > 0.05). Conclusion: School-based interventions and school–parent collaboration are needed to promote balanced digital use, healthy sleep habits, and physical activity among students. This study is limited by its cross-sectional design, self-reported data, and small single-school sample, which restrict causal inference and generalizability.